Lipid Profile of Chicken (Gallus domesticus) in Response to Dietary Supplementation of Garlic (Allium sativum) - Prasad, R.; Rose, M.K.; Virmani, M.; Garg, S.L.; Puri, J.P. (International Journal of Poultry Science, 2009)
Garlic is widely distributed and used in all parts of the world as a spice and herbal remedy for various ailments, including its role in diabetes, blood coagulation, metabolism and immune functions. But there are scanty reports regarding its effect on lipid profile in poultry. The study was conducted on 24 broiler chicks divided randomly into 3 groups, each group consisting of 8 birds. Group I birds were used as control kept on conventional diet. Group II and III birds were supplemented with garlic at the rate of 1.5 and 3.0%, respectively (on dry matter basis) of total feed for a period of 8 weeks. Lipid profile viz. total cholesterol, triglycerides, Low Density Lipoprotein (LDL), Very Low Density Lipoprotein (VLDL) and High Density Lipoprotein (HDL) were studied. The total cholesterol, triglycerides, LDL and VLDL were significantly decreased, while HDL was significantly increased by garlic supplementation in chicken upto 8 weeks of age in comparison to control group. There was a significant increase in total cholesterol with advancement of age and this increase was prevented by garlic supplementation in feed. The present findings suggest that the garlic supplementation in feed is effective in regulation of lipid metabolism, which is the predisposing factor for the coronary heart diseases. Further, our results suggest that the garlic is effective in regulation of cholesterol level with advancement of age. In conclusion, garlic is effective in regulation of lipid profile.